16. SOME FACTORS RELATED TO THE QUALITY OF PATIENT RESTROOMS AT THE NATIONAL OBSTETRICS AND GYNECOLOGY HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: To identify some factors related to the quality of patient restrooms.Subject and methods: A cross-sectional descriptive study was conducted on all 165 patient restrooms, with a total of 660 evaluations at the National Obstetrics and Gynecology Hospital in 2023. The overall quality of the restrooms was considered up to standard when all aspects were rated as satisfactory.Results: Restrooms with overall satisfactory quality accounted for 21.8%. Restrooms in buildings A, BC, H and K were 7.6 times more likely to meet high-quality standards compared to restrooms in buildings D, G, and the requested clinics. Restrooms that completed the sanitation checklist were 33.6 times more likely to be of high quality compared to those that did not complete the checklist. Outpatient restrooms were 4.46 times more likely to meet high-quality standards than inpatient restrooms (p < 0.05). Factors include: deteriorating facilities, lack of restrooms, shortage of cleaning staff, cleaning staff lacking knowledge and awareness of restroom sanitation, and poor restroom usage habits of patients increase the risk of restrooms not meeting standards.Conclusion: Factors related to facilities; restroom cleaning activities, inspection and supervision; the number and quality of cleaning staff; patient restroom usage awareness and characteristics; and hospital support are associated with the quality of patient restrooms. Therefore, the hospital needs to intervene based on these risk factors to improve the quality of patient restrooms.
Keywords: Quality, toilets, patients, relationships.